Intervenciones telepsicológicas con deportistas cubanos de alto rendimiento durante la pandemia COVID-19 - Montoya Romero, C.; Suarez Armas, C.; González Carballido, L. G. (Revista Cubana de medicina del deporte y la cultura fisica, 2020)
Introduction: The confinement conditions, as a measure to avoid the spread of COVID-19, have psychologically impacted the athletes of the Cuban sports movement. During this stage, the specialists of the Institute of Medicine of the Sport (IMD) Psychology Subdirectorate carried out telepsychological coverage through information and communication technologies.